Cumulative Causation - William A. Jackson (International Encyclopedia of Human Geography, 2nd edn, 2020)
Cumulative causation arises when a process is self-reinforcing and grows ever stronger, so that it does not equilibrate. It will continue indefinitely unless it is checked by outside intervention or leads to a crisis and systemic breakdown. Ideas of cumulative causation have numerous applications in economics and other social sciences, investigated by authors such as Nicholas Kaldor, Gunnar Myrdal and Albert Hirschman. In human geography, cumulative processes have particular relevance for inequalities between rich and poor regions, implying that without intervention the gaps will widen. This article discusses the nature of cumulative causation, examines its general features, and assesses its geographical consequences at national and global levels.
https://doi.org/10.1016/B978-0-08-102295-5.01001-5
Keywords: B41; B50; O10; R11; R58; 330; increasing returns; vicious and virtuous circles; disequilibrium; Matthew effect; unequal development; regional policies